Fitohormonas promotoras en el crecimiento vegetal en la producción del cultivo de banano - Meléndez Cerezo, Joel Edison (2021)
In banana cultivation, you always have to look for a better quality and an increase in production, taking into account that the main thing of everything is to produce with quality. The main limitation of these are factors related to the climate, because the excess of rain and the lack of it makes the plants stress, therefore hormones are used, to maintain an excellent production and supply the plant, which in its natural state it produces these hormones, but in critical times it is difficult to produce them for this because it generates stress. Generally, hormones are active in very small amounts and are produced by the plant, but in climatic stress they are used as a biostimulant for the plant to finish its physiological process as plant growth that are caused by auxins and cell division for stem thickness by cytokinins, even more gibberellins lengthen the stem and also stimulates the flowers and the fruit.